Human skin model serving in electrical stimulation of Anterior Tibial Artery - Shafi , Hina; Ashqeen , Iqra; Kanwal , Madiha; Mohy Uddin , Zia (International Journal of Endorsing Health Science Research, 2013)
Cardiac activities are one of the vital signs of life. To monitor these activities there are several methods including electrocardiography (ECG), photo plysthesmography, electrical impedance plythesmography. The purpose of the paper is to design external electrodes placed on the uppermost skin layer called stratum corneum which are capable of stimulating human anterior tibial artery without damaging it. This artery is present along the length of human tibia bone or shin bone .The designed electrodes are diminutive enough to attach with any easily wearable device. These electrodes when supplied with potential stimulate the artery helping in the procedure of electrical impedance plethysmography, this method is simple and low-cost.On the other hand, Electrical Impedance Plethysmography appears to be the most practical solution as compared to the above mentioned techniques of monitoring cardiovascular activities By varying electrode size and the distance between the electrodes we can skillfully judge the point where the electric field reaches the artery. The simulation of this model is done by Comsol Multiphysics.